Prevalence of Canine Obesity, Obesity-Related Metabolic Dysfunction, and Relationship with Owner Obesity in an Obesogenic Region of Spain - Montoya-Alonso, J. Alberto; Bautista-Castaño, Inmaculada; Peña, Cristina; Suárez, Lourdes; Juste, M. Candelaria; Tvarijonaviciute, Asta (Frontiers in Veterinary Science, 2017)
The main objective of this study was to evaluate the prevalence of canine obesity and obesity-related metabolic dysfunction (ORMD) in the obesogenic area in Spain. The prevalence of overweight/obesity among owners of obese pets was also evaluated. In the sample population studied (93 client-owned dogs), 40.9% of dogs presented obesity (body condition score 7–9/9), 40.9% of dogs presented hypertension, 20.4% of dogs presented fasting hypertriglyceridemia, 20.4% fasting hypercholesterolemia, and 5.4% of dogs presented fasting hyperglycemia. The overall prevalence of ORMD was of 22.6%. Seventy-eight percent of overweight/obese owners had overweight/obese dogs (P < 0.001) including all dogs diagnosed with ORMD. In conclusion, in the studied obesogenic region of Spain, the prevalence of canine obesity and ORMD was shown to be elevated and related to the presence of overweight/obesity in owners. All dogs with ORMD were owned by overweight/obese persons. These results provide new inputs for future studies highlighting the relationship between owner and pet obesity and indicating the need of further efforts to control and reduce obesity prevalence in both.